2017
DOI: 10.2215/cjn.06080616
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 Inhibition in the Diabetic Kidney—From Mechanisms to Clinical Outcome

Abstract: Diabetic kidney disease not only has become the leading cause for ESRD worldwide but also, highly contributes to increased cardiovascular morbidity and mortality in type 2 diabetes. Despite increased efforts to optimize renal and cardiovascular risk factors, like hyperglycemia, hypertension, obesity, and dyslipidemia, they are often insufficiently controlled in clinical practice. Although current drug interventions mostly target a single risk factor, more substantial improvements of renal and cardiovascular ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
159
2
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(177 citation statements)
references
References 55 publications
4
159
2
12
Order By: Relevance
“…Our analysis also showed that the magnitude of UACR reduction was similar in patients treated with and without RASi at baseline. This is in contrast to previous literature in which it has been proposed that SGLT-2 inhibition with concomitant RASi may synergistically boost the alternative RAS axis, leading to upregulation of angiotensin (1)(2)(3)(4)(5)(6)(7). 37 In our analysis, we did not find modulation by RASi or any indication of a possible synergistic effect, thus the effect of RASi is probably smaller.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our analysis also showed that the magnitude of UACR reduction was similar in patients treated with and without RASi at baseline. This is in contrast to previous literature in which it has been proposed that SGLT-2 inhibition with concomitant RASi may synergistically boost the alternative RAS axis, leading to upregulation of angiotensin (1)(2)(3)(4)(5)(6)(7). 37 In our analysis, we did not find modulation by RASi or any indication of a possible synergistic effect, thus the effect of RASi is probably smaller.…”
Section: Discussioncontrasting
confidence: 99%
“…Sodium-glucose co-transporter-2 (SGLT-2) inhibitors, such as dapagliflozin, lower blood glucose levels by blocking glucose reuptake in the proximal tubule, resulting in urinary glucose excretion. 1 Beyond their glucose-lowering effect, evidence from recent cardiovascular (CV) outcomes trials (CVOTs) [2][3][4] indicates that whereas the effects of SGLT-2 inhibitors on major adverse CV events might be limited to patients with established CV disease, the beneficial effects on heart failure and renal function might be applicable to a broad population of patients with type 2 diabetes (T2D). [5][6][7] In particular, in these trials, SGLT-2 inhibitors delayed the progression of nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Selective SGLT2 inhibitors have been developed to reduce glucose reabsorption in renal proximal tubules improving glycemic control in patients with T2DM [23]. As this has the effect of redistributing the glucose out of the PTC and into the lumen/urine, we undertook this study to determine the effect of this redistribution on intrarenal RAS activation, blood pressure, and kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it was associated with a statistically significant lower incidence rate of macroalbuminuria (38%), doubling of serum creatinine and eGFR# 45 ml/min per 1.73 m 2 (44%), and initiation of dialysis (55%). In addition, as we mentioned above, the sodium glucose transport type 2 inhibitor also can ameliorate the autophagy process that is down regulated in the proximal tubular cells due to hyperglycemia [57][58][59][60][61].…”
Section: Sodium-glucose-co Transporter (Sgl2) Blockersmentioning
confidence: 99%